IMPLIKASI MODEL BIOEKONOMI TERHADAP MANAJEMEN PERIKANAN TANGKAP: STUDI KASUS DI PANTAI SELATAN YOGYAKARTA - Suadi Suadi; Soeparno Soeparno; Retno Widianingroem (Universitas Gadjah Mada, 2003)
Small-scale marine capture fisheries have contributes to community welfare at Yogyakarta’s south coast. Government has planned some programs to develop fisheries. The development supposed only at rational effort in which fishers still gain advantages. Precautionary approach using bio-economic model of Gordon-Schaefer was applied to analyze the issue. The linear regression model of catch per unit of effort (C/f) (CPUE) and effort (f) was C/f = 59,851 – 0,0005f (R2 = 82, 71%). Fish price assumed at Rp 7,735.19 /kg with operational cost of Rp 59,835.67/trip. Total revenue and effort at maximum sustainable yield was predicted at Rp 13,396 billion and 56,860 trip (equals to 327 vessels), respectively. Fisher income at this level was Rp 167,774.51/trip/vessel. Fish exploration level in this area has already closed to total allowable catch. Free access equilibrium in which cost is equal to revenue might reach at effort of 102,231 trip (equals to 568 vessels). Managing fisheries at maximum economic yield might rise fisher income 17.83% comparing to maximum sustainable yield, but total revenue decreased 1.77% at 56.13% of existing effort. Some management strategies should be promoted and regulated for the fishery exploitation. Based on the results, those possible strategy were 1) limiting investment through regulation and permission; 2) improvement of fishers productivity through technology improvement to exploit under-used fish resources; 3) expanding the fisheries activity to offshore through harbor development and social preparation; 4) marketing improvement through revitalization of fish action; 5) improving hadling and post harvest fish technology through training and extension; 6) the increasing of bargaining position through empowering fishers group; 7) promoting alternate incomes through integrated coastal tourism development; and 8) avoiding competition and conflict through developing Java’s south coast cooperation. Participatory approach in planning, developing and evaluating should be promoted to develop fishery a southern coast of Yogyakarta.